2001
DOI: 10.1046/j.1365-2648.2001.01657.x
|View full text |Cite
|
Sign up to set email alerts
|

Are people with learning disabilities able to contribute to focus groups on health promotion?

Abstract: We conclude that focus groups are an effective method of conducting exploratory research with adults with learning disabilities in the community, however, ability to participate with other members may be a limiting factor. Furthermore, special arrangements may need to be made for groups to be successful, including the use of an interpreter. The preparation of the moderator is also an important factor in group success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Focus groups are commonly used as a research method for conducting research with people with ID [20][21][22]. This is because the focus groups include a large amount of the participants' opinions, suggestions and ideas, and do not require written language skills.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Focus groups are commonly used as a research method for conducting research with people with ID [20][21][22]. This is because the focus groups include a large amount of the participants' opinions, suggestions and ideas, and do not require written language skills.…”
Section: Methodsmentioning
confidence: 99%
“…We found that focus group interviews were an appropriate method commonly used as a research method for conducting research with people with ID [20][21][22]. The health promotion intervention program is part of the Public Health Program in a mid-to large-sized municipality in Norway.…”
Section: Designmentioning
confidence: 99%
“…Owing to the client's cognitive ability, checking whether communication has been understood is advisable by asking for feedback throughout the programme (Fraser and Fraser, 2001). This could be carried out using techniques such as Buzz groups, which promote interaction (Hafler, 2003), food diaries to record and evaluate nutrition, and role play as outlined by Lindsay and Michie (1998).…”
Section: Evaluation Methodsmentioning
confidence: 99%
“…Therefore, extreme care must be taken to ensure that health promotion messages are understood as positive life changes (Hart, 2007). Consequently, to support and include people with intellectual disability within the health promotion programme, their existing knowledge of how to maintain health needs to be identified and assessed (Fraser and Fraser, 2001). This can be achieved using the Nutritional and Activity Knowledge Scale (NAKS) designed by Illingworth et al (2003), which identifies clients' knowledge and understanding of foods and nutrition.…”
Section: Social Change Approachmentioning
confidence: 99%
See 1 more Smart Citation